Performance Analysis of Client-Side Rendering in a Hybrid LMS using Core Web Vitals Under Diverse Network Conditions - Nindia Prameswari Putri Cahyono; Hoiriyah Hoiriyah; Aang Kisnu Darmawan; Rofiuddin Rofiuddin (Universitas Islam Indragiri, 2026)
The implementation of a Hybrid Learning Management System (Hybrid LMS), which integrates structured learning and self-directed learning within a single platform, presents challenges in website performance, particularly in the implementation of Client-Side Rendering (CSR). This study aims to analyze the performance of Client-Side Rendering in a Hybrid LMS website using Core Web Vitals under diverse network conditions. A quantitative descriptive approach was employed, with laboratory-based testing conducted using Google Lighthouse. Performance evaluations were carried out three times under each network condition—morning, afternoon, and evening—and the results were compared using the average values of each performance metric. The primary contribution of this study is the provision of empirical evidence regarding the performance stability of Client-Side Rendering in a Hybrid LMS under varying network conditions. The findings indicate that the Hybrid LMS website maintains relatively stable performance across different network environments. The best Largest Contentful Paint (LCP) value was 1.2 seconds, the best Cumulative Layout Shift (CLS) value was 0, and the best Total Blocking Time (TBT) was 500 ms. Furthermore, Lighthouse audits consistently reported Accessibility, Best Practices, and SEO scores of 89, 100, and 92, respectively, across all testing locations. Although certain network conditions resulted in increased Total Blocking Time (TBT) and Speed Index values, the overall results demonstrate that the Hybrid LMS website provides a sufficiently optimized user experience to effectively support digital learning activities.